Chinese medicine treatment for menopausal symptoms in the UK health service: Is a clinical trial warranted?. Issue 2 (February 2015) - Scheid, Volker; Tuffrey, Veronica; Weijburg, Thomas; Bovey, Mark; Ward, Trina
Highlights A pilot study exploring effects of real-life Chinese medicine. Significant reduction of symptoms on MenQoL and Green scales. No adverse effects. We recommend a pragmatic RCT to provide more solid evidence on effectiveness.